Membiayai masa depan: Analisis dampak utang luar negeri dan investasi asing terhadap pembangunan sosial di Indonesia - Yuliarti, Yuliarti; Akmal, Artha Dini; Maani, Karjuni Dt. (Nur Science Institute, 2024)
The development paradigm in the world today is not only about economic growth but also discusses social development that is expected to create prosperity; even the first goal of sustainable development agreed upon by all countries is poverty alleviation. As a developing country, overcoming this problem is inseparable from external assistance. For decades, foreign debt and investment have financed Indonesia's growth. This study investigates the direct and indirect effects of foreign debt and foreign investment on poverty, with economic growth as an intervening variable. This study uses a quantitative methodology, using the path analysis method in the data processing. The results state that the foreign debt variable hurts monetary development. Through economic growth, foreign debt also has a negative direct and indirect impact on poverty in Indonesia. The foreign investment variable has no direct or indirect effect on poverty in Indonesia and does not impact economic growth. In addition, this study shows that Indonesian poverty is not affected by economic growth.